-7(7x+6)-3(x-9)=

Simple and best practice solution for -7(7x+6)-3(x-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(7x+6)-3(x-9)= equation:


Simplifying
-7(7x + 6) + -3(x + -9) = 0

Reorder the terms:
-7(6 + 7x) + -3(x + -9) = 0
(6 * -7 + 7x * -7) + -3(x + -9) = 0
(-42 + -49x) + -3(x + -9) = 0

Reorder the terms:
-42 + -49x + -3(-9 + x) = 0
-42 + -49x + (-9 * -3 + x * -3) = 0
-42 + -49x + (27 + -3x) = 0

Reorder the terms:
-42 + 27 + -49x + -3x = 0

Combine like terms: -42 + 27 = -15
-15 + -49x + -3x = 0

Combine like terms: -49x + -3x = -52x
-15 + -52x = 0

Solving
-15 + -52x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -52x = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -52x = 0 + 15
-52x = 0 + 15

Combine like terms: 0 + 15 = 15
-52x = 15

Divide each side by '-52'.
x = -0.2884615385

Simplifying
x = -0.2884615385

See similar equations:

| 7=-5+6(-8x+2) | | -11=3x+7-3x | | 5y-11-2y^9=0 | | 25x-3=35x+3 | | 7x+9+3y+4=143 | | 5x+39=3 | | 6x=4(5+x) | | 0=2x^2-8x+3 | | -4(4+a)= | | m+14=-3 | | 5(3+6x)-2=163 | | (a+2)/(2)=-1 | | 10+6q=14+5q | | 37-6x=61-2x | | -3(6y-7)-y=-3(y-2) | | 5x^9*2u*2u^2x^9= | | 7(7n+3)-10(n-9)= | | 3/10t=6 | | y-13=-4 | | 0=8r-3r | | 2(a+1)=3(a-2)-a | | 3m+6=-6+m | | 10+m/2=6 | | q=-45/-3 | | 2(x+4)-5(x-3)=34 | | 6x-6-8=4x-4+6-2x | | 8+7x=78 | | 5n+7n=-12 | | 6+15y-3=8y+107-6y | | 5(a-12)-24=3(s+2) | | 5x-7-3x=19 | | (8t+30)+(-2-16)=-22 |

Equations solver categories